Three-point Block Algorithm For Approximating Duffing Type Differential Equations - Ahmad Fadly Nurullah Rasedee; Mohammad Hasan Abdul Sathar; Najwa Najib; Nurhidaya Mohamad Jan; Siti Nor Aini Mohd Aslam; Siti Munirah Mohd (Horizon Research Publishing, 2024)
Indexed by Scopus